2000
DOI: 10.1016/s0006-3495(00)76456-3
|View full text |Cite
|
Sign up to set email alerts
|

Protein Diffusion in Living Skeletal Muscle Fibers: Dependence on Protein Size, Fiber Type, and Contraction

Abstract: Sarcoplasmic protein diffusion was studied under different conditions, using microinjection in combination with microspectrophotometry. Six globular proteins with molecular masses between 12 and 3700 kDa, with diameters from 3 to 30 nm, were used for the experiments. Proteins were injected into single, intact skeletal muscle fibers taken from either soleus or extensor digitorum longus (edl) muscle of adult rats. No correlation was found between sarcomere spacing and the sarcoplasmic diffusion coefficient (D) f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
122
1
2

Year Published

2004
2004
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 165 publications
(140 citation statements)
references
References 57 publications
15
122
1
2
Order By: Relevance
“…In the literature, several factors that influence the diffusion properties of a muscle tissue have been discussed: fiber type and composition (7), myofilament lattices (22), temperature (23), and cell volume (24). It seems obvious that the diffusional anisotropy of musculature is the result of physical barriers due to the muscular architecture.…”
Section: Discussionmentioning
confidence: 99%
“…In the literature, several factors that influence the diffusion properties of a muscle tissue have been discussed: fiber type and composition (7), myofilament lattices (22), temperature (23), and cell volume (24). It seems obvious that the diffusional anisotropy of musculature is the result of physical barriers due to the muscular architecture.…”
Section: Discussionmentioning
confidence: 99%
“…The diffusion of Mb in skeletal muscle has been of particular interest because of its role in reversibly binding O 2 and therefore serving as a temporary O 2 store and facilitating O 2 diffusion (reviewed in Wittenberg and Wittenberg, 2003). Several studies have found that D of Mb in muscle fibers is about 1/6 to 1/10 of that in aqueous solution (Baylor and Pape, 1988;Jurgens et al, 1994;Papadopoulos et al, 1995;Papadopoulos et al, 2000;Papadopoulos et al, 2001). Measurements of protein diffusion in skeletal muscle from frog (Maughan and Lord, 1988;Maughan and Godt, 1999) and cultured mammalian fibers (Arrio-Dupont et al, 1997;Arrio-Dupont et al, 2000) yielded D values that were minimally 1/3 lower than that in water, and in many cases much more dramatically reduced.…”
Section: The Intracellular Environment Of Muscle Has Characteristics mentioning
confidence: 99%
“…If the dye is effectively bound to the protein the ANS-fluorescein separation should be less than the diameter of apoMb (∼3.5 nm) (Papadopoulos et al 2000). Because the Förster critical distance, R 0 , for the ANS-fluorescein pair is 5 nm (Sassaroli et al 1984), the ANS → fluorescein energy transfer efficiency should be higher than 90%, and virtually all the ANS fluorescence would be quenched.…”
Section: Characterization Of Labeled Apombmentioning
confidence: 99%